Linguo-cultural value of 忍 'patience' in traditional and modern Chinese culture - Yana A. Volkova; Svetlana G. Korovina (Peoples' Friendship University of Russia (RUDN University), 2024)
The article outlines a gap in the comprehensive study of values and evaluation processes in human consciousness, emphasising how these processes are aligned with linguo-cultural concepts. The research aims to investigate the evolving cultural value of忍 (rěn) 'patience' in Chinese culture, highlighting the significance of understanding these transformations in the context of axiological linguistics. A mix of qualitative and quantitative methods to explore the cultural and linguistic significance of忍 (rěn) in Chinese culture was employed. Lexicographical, contextual, and semantic analyses, along with cultural commentary, were applied to describe the multifaceted meanings of忍 (rěn). The study also used a two-part experimental approach: first, a survey collected diverse Chinese perceptions of忍 (rěn) through adjectives/nouns, and then an evaluative experiment with bipolar semantic scales measured attitudes towards patience along various dimensions. The findings point out shifts in the modern interpretation of忍 (rěn) within Chinese culture. While traditional values emphasise endurance and resilience, contemporary perspectives acknowledge the complexity of patience, recognising its strategic, interpersonal, and ethical dimensions. The concept of patience is evolving to encompass adaptability, compromise, and long-term vision, reflecting changing societal values and the influence of globalisation. Despite these shifts, the significance of忍 (rěn) in fostering personal growth, social harmony, and ethical conduct remains central to contemporary Chinese values and societal norms. The results contribute to a deeper understanding of the transformation of cultural values within society, illustrating how linguistic methods can be employed to study their evolving nature.